2011
DOI: 10.1007/s10851-011-0275-1
|View full text |Cite
|
Sign up to set email alerts
|

Multiplicative Calculus in Biomedical Image Analysis

Abstract: We advocate the use of an alternative calculus in biomedical image analysis, known as multiplicative (a.k.a. non-Newtonian) calculus. It provides a natural framework in problems in which positive images or positive definite matrix fields and positivity preserving operators are of interest. Indeed, its merit lies in the fact that preservation of positivity under basic but important operations, such as differentiation, is manifest. In the case of positive scalar functions, or in general any set of positive defin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
63
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 117 publications
(65 citation statements)
references
References 31 publications
(66 reference statements)
0
63
0
2
Order By: Relevance
“…We approximate the integral between two points by assuming a linear relationship and storing the preintegrated values in a lookup table. Note that the compositing of the medium color is fully multiplicative, we therefore utilize the multiplicative integral of multiplicative calculus [50,51] given by:…”
Section: Compositingmentioning
confidence: 99%
“…We approximate the integral between two points by assuming a linear relationship and storing the preintegrated values in a lookup table. Note that the compositing of the medium color is fully multiplicative, we therefore utilize the multiplicative integral of multiplicative calculus [50,51] given by:…”
Section: Compositingmentioning
confidence: 99%
“…For more information about multiplicative metric space and best proximity point theorems see [6,7,8,9] In this paper, we established some new existence and convergence theorems of iterates of best proximity points for multiplicative MT -cyclic contractions.…”
Section: Remarkmentioning
confidence: 99%
“…From then on, several authors have reported some important fixed point results in the framework of multiplicative metric spaces (see [2,3,[5][6][7]). In 2016, Agarwal et al [1] pointed out the relation between the multiplicative metric spaces and the standard metric spaces.…”
Section: Introductionmentioning
confidence: 99%